PERANCANGAN WEBSITE SEKOLAH PENGOLAAN DATA SISWA - Dwi Kartinah (Asosiasi Dosen Muda Indonesia, 2024)
The rapid development of information and communication technology (ICT) has significantly influenced various aspects of human life, including the education sector. Schools, as educational institutions, require efficient and accurate student data management to support administrative and academic activities. However, many schools still rely on manual methods, which are time-consuming, prone to errors, and inefficient in handling large amounts of data. This research focuses on designing and implementing a web-based Student Data Management System. The application leverages PHP as the server-side programming language, MySQL for database management, and CSS for an attractive and user-friendly interface. The system includes features such as adding, updating, and viewing student data, facilitating centralized and structured data management. The design follows the Software Development Life Cycle (SDLC) method, including planning, design, implementation, and testing stages. The results demonstrate that the system can effectively replace manual data management methods, offering a more efficient and modern solution for schools. However, further development, particularly in responsive design for mobile devices, is suggested to enhance user experience.